Average Error: 0.0 → 0.0
Time: 4.0s
Precision: 64
$\left({2}^{x} - {2}^{2}\right) + 6$
$6 + \left({2}^{x} - {2}^{2}\right)$
\left({2}^{x} - {2}^{2}\right) + 6
6 + \left({2}^{x} - {2}^{2}\right)
double f(double x) {
double r24760367 = 2.0;
double r24760368 = x;
double r24760369 = pow(r24760367, r24760368);
double r24760370 = pow(r24760367, r24760367);
double r24760371 = r24760369 - r24760370;
double r24760372 = 6.0;
double r24760373 = r24760371 + r24760372;
return r24760373;
}


double f(double x) {
double r24760374 = 6.0;
double r24760375 = 2.0;
double r24760376 = x;
double r24760377 = pow(r24760375, r24760376);
double r24760378 = pow(r24760375, r24760375);
double r24760379 = r24760377 - r24760378;
double r24760380 = r24760374 + r24760379;
return r24760380;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\left({2}^{x} - {2}^{2}\right) + 6$
2. Final simplification0.0

$\leadsto 6 + \left({2}^{x} - {2}^{2}\right)$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "pow(2,x)-pow(2,2)+6"
(+ (- (pow 2.0 x) (pow 2.0 2.0)) 6.0))